2016
DOI: 10.1016/j.carbon.2015.12.023
|View full text |Cite
|
Sign up to set email alerts
|

High stiffness nano-composite fibres from polyvinylalcohol filled with graphene and boron nitride

Abstract: Here we describe using nanosheets of both graphene and boron nitride, produced by liquid phase exfoliation, as fillers in composite fibres. The fibres were prepared by coagulation spinning using polyvinylalcohol as a matrix. We obtained good quality fibres with diameter and nanosheet volume fraction which could be controlled via the ratio of nanosheet to polymer injection rates. The mechanical stiffness (modulus, Y) and strength, σB, increased relatively slowly with volume fraction (dY/dVf 160 GPa and dσB/dVf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 101 publications
1
25
0
Order By: Relevance
“…d–f) SEM images; g) stress strain curves; h) Young's modulus and i) tensile strength of PVA‐BNNS fiber and PVA‐graphene fibers as a function of volume fraction. Reproduced with permission . Copyright 2016, Elsevier.…”
Section: Assembliesmentioning
confidence: 99%
See 1 more Smart Citation
“…d–f) SEM images; g) stress strain curves; h) Young's modulus and i) tensile strength of PVA‐BNNS fiber and PVA‐graphene fibers as a function of volume fraction. Reproduced with permission . Copyright 2016, Elsevier.…”
Section: Assembliesmentioning
confidence: 99%
“…Most recently, Coleman's group also reported fabrication of BN‐based fibers where coagulation‐spinning method was used . In their study, polyvinyl alcohol (PVA)‐BNNS fibers were fabricated using PVA as the fiber matrix and highly concentrated BNNS as the filler.…”
Section: Assembliesmentioning
confidence: 99%
“…A clear decrease in both properties occurred at 1.0 wt%, a drop by 5.3%, and 4.0% in EL and T, respectively. Such decreases at high loading content are often observed and associated to the agglomeration of the nanomaterials 1,67 suggesting the mixing process used here is not optimized for high loadings.…”
Section: Tensile Propertymentioning
confidence: 99%
“…[1][2][3][4][5] Graphene nanoplatelets (GNPs) are regarded as short stacks of less than 10 graphene layers, and may be purchased at a relatively low cost. 2,[6][7][8] GNPs are widely used as nanoadditives for advanced composites, 1,9-11 electrodes in advanced batteries 12 and ultra/super capacitors, 13,14 and the conductive component in specialty coatings 15 or adhesives.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the second nanomaterial can not only improve the properties of the nanocomposites, but also increase the nanomaterials’ dispersion within the matrix. Hybrid nanomaterials such as clay with MWNT, graphene with MWNT, and MWNT with carbon black have exhibited remarkable synergetic effects while enhancing the properties of the nanocomposites . Zhang and coworkers, reported that the tensile strength of poly(vinyl alcohol) composites with MWNT and a hybrid graphene filler (0.6 wt %) were 20% and 34% higher than those of composites filled with the same amounts of MWNT and graphene alone, respectively.…”
Section: Introductionmentioning
confidence: 99%